2019
DOI: 10.1002/path.5281
|View full text |Cite
|
Sign up to set email alerts
|

Tspan8 is expressed in breast cancer and regulates E‐cadherin/catenin signalling and metastasis accompanied by increased circulating extracellular vesicles

Abstract: Tspan8 exhibits a functional role in many cancer types including pancreatic, colorectal, oesophagus carcinoma, and melanoma. We present a first study on the expression and function of Tspan8 in breast cancer. Tspan8 protein was present in the majority of human primary breast cancer lesions and metastases in the brain, bone, lung, and liver. In a syngeneic rat breast cancer model, Tspan8+ tumours formed multiple liver and spleen metastases, while Tspan8− tumours exhibited a significantly diminished ability to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 65 publications
0
29
0
3
Order By: Relevance
“…We hypothesized that EVs secreted by metastatic and nonmetastatic NSCLC cells carry proteins that can distinguish these cells and function as diagnostic biomarkers of metastatic NSCLC. To test this hypothesis, we used mass spectrometry (MS) to detect EV proteins that were differentially expressed in two mouse NSCLC cell lines with metastatic and nonmetastatic phenotypes and found that EV expression of tetraspanin-8 (Tspan8) was associated with NSCLC invasiveness, in keeping with findings that its elevated cellular expression is associated with metastasis (10)(11)(12). Subsequent analysis found that intersectin-2 (Itsn2) expression, which regulates Tspan8 packaging into EVs (13,14), was increased in the metastatic NSCLC cell line and that overexpression of Itsn2 increased EV Tspan8 abundance and EV-enhanced NSCLC cell invasion.…”
Section: Introductionmentioning
confidence: 88%
“…We hypothesized that EVs secreted by metastatic and nonmetastatic NSCLC cells carry proteins that can distinguish these cells and function as diagnostic biomarkers of metastatic NSCLC. To test this hypothesis, we used mass spectrometry (MS) to detect EV proteins that were differentially expressed in two mouse NSCLC cell lines with metastatic and nonmetastatic phenotypes and found that EV expression of tetraspanin-8 (Tspan8) was associated with NSCLC invasiveness, in keeping with findings that its elevated cellular expression is associated with metastasis (10)(11)(12). Subsequent analysis found that intersectin-2 (Itsn2) expression, which regulates Tspan8 packaging into EVs (13,14), was increased in the metastatic NSCLC cell line and that overexpression of Itsn2 increased EV Tspan8 abundance and EV-enhanced NSCLC cell invasion.…”
Section: Introductionmentioning
confidence: 88%
“…TSPAN8 protein is present in the majority of human primary breast cancer lesions and metastases in different organs (the brain, bone, lung and liver). TSPAN8 enhances cell-cell adhesion, proliferation, mesenchymal-epithelial transition, radiation resistance and extracellular vesicle release [78].…”
Section: Breast Cancersmentioning
confidence: 99%
“…Evidências crescentes sugerem que o TSPAN8 promove a migração, invasão e metástase de células tumorais em vários tipos de câncer humano, incluindo câncer colorretal, ovariano e gástrico, hepatocarcinoma, adenocarcinoma pancreático e glioma (GESIERICH et al, 2005;PAN et al, 2015;PARK et al, 2016;VOGLSTAETTER et al, 2019).…”
Section: Tspan8unclassified
“…A respeito de nossos resultados, embora não significativos TSPAN8 exibiu uma diminuição do transcrito primário nas amostras tumorais em comparação com tecido normal. Isto evidencia contraste com o trabalho do Voglstaetter e colaboradores que avaliaram a expressão de mRNA de TSPAN8 por RT-qPCR em 15 amostras de câncer mamário sendo 01 tecido normal, 07 tumores primários e 07 metástases de pulmão e linfonodos, relatando uma expressão aumentada nos espécimenes metastáticos, intermediaria em tumores primários e mínima no tecido normal (VOGLSTAETTER et al, 2019). Adicionalmente, isto também foi dissemelhante para câncer colorretal e para de ovário, dado que foram encontrados níveis elevados de transcrito primário e proteína nas amostras tumorais em comparação com os respetivos controles (PARK et al, 2016;ZHANG et al, 2020).…”
Section: Tspan8unclassified
See 1 more Smart Citation